Ophiocordyceps linyphiidarum sp. nov., a newly discovered spider-pathogenic fungus from China - Yang, Yu; Jayawardena, Ruvishika S.; Hyde, Kevin D.; Lu, Yong-Zhong; Mapook, Ausana; Nilthong, Somrudee; Xie, Shu-Qiong; Xiao, Yuan-Pin (Phytotaxa, 2025)
Spider-pathogenic fungi are predominantly found in Cordycipitaceae, with only rare occurrences in Ophiocordycipitaceae. Among the Ophiocordycipitaceae, Ophiocordyceps is the largest genus and is known for its ecological adaptability and broad host range and potential applications in sustainable pest management. Ophiocordyceps species thrive in tropical and subtropical regions, particularly in southwestern China, a biodiversity hotspot and key region for conservation of fungal diversity. During a survey in Southwest China, a new species, Ophiocordyceps linyphiidarum was identified. This species is distinguished from other Ophiocordyceps species by its specific spider host (Linyphiidae), and unique morphological characteristics, including longer polyblastic phialides and polymorphic, non-velutinous conidia. Phylogenetic analyses based on combined datasets of SSU, LSU, ITS, tef-1α, rpb1, and rpb2 further support its distinctiveness from related species. The discovery of O. linyphiidarum contributes to our understanding of ecosystem dynamics, supports climate-resilient biological control strategies, and emphasizes the value of exploring fungi as part of nature-based solutions for sustainable production and ecosystem health. The new species is formally described, illustrated, and compared with morphologically similar taxa.